REHABILITATION AND MANAGEMENT OF CORAL REEFS IN SOUTHERN QUI NHON BAY (SOUTH VIETNAM) - Tuan, Vo Si; Hoa, Nguyen Xuan; Hoang, Phan Kim; Ben, Hoang Xuan (Vietnam Journal of Marine Science and Technology, 2009)
An extensive rehabilitation was practiced during 2002 - 2004 in southern Qui Nhon bay of coastal Binh Dinh province where coral reefs had suffered serious degradation due to coral mining, destructive fishing and overfishing. The first experiment indicated that the nearshore reefs in the western part could not be rehabilitated due to environment change during rainy season with large discharge of sediment and freshwater. Transplanted hard corals adapted well in southern part of island Hon Ngang and Hon Nhan with the techniques that used dead coral substratum, concrete plates and revered tubs as the attachments of corals. Survival rate of branch corals Acropora was quite high in dry season (85- 100%) but reduced during rainy season (60-80%). Meanwhile Porites nigrescens presented good adaptation to environment seasonal change. The corals which were fixed with steel sticks on reefplatform had low survival rate due to sediment movement in north-east monsoon. The concurrent site management with strong supports from local government and communities has brought positive effectiveness of reef rehabilitation thank to not only coral transplantation but also natural recovery. Foliose corals belonging to Montipora, Echinopora. Pachyseris. Echinopora and branch Acropora, Porites play an important role of natural rehabilitation. The activities, however, require hard work and expensive cost as well as sympathy oflocal people.